Current state of knowledge about spironolactone-induded gynecomastia. Review 2024 - Oliwia Kamila Iszczuk; Julia Silldorff; Tomasz Fura; Marcin Dudek; Radosław Zaucha; Magdalena Gajkiewicz; Zuzanna Felińska; Małgorzata Zając; Stanisław Anczyk (Nicolaus Copernicus University in Toruń, 2024)
Spironolactone, a potassium-sparing diuretic, acts as an aldosterone antagonist but also has anti-androgen properties, leading to increased estrogen levels in the body. It can cause gynecomastia in men by blocking the production of androgens, preventing androgens from binding to specific receptors, and rising levels of both total and free estrogen.  Numerous scientific articles and clinical cases have been analyzed and confirmed this statement. Evidence for gynecomastia with mineralocorticoid receptor antagonist usage was of high quality.Clinicians are advised to monitor patients taking these medications for developing gynecomastia and to consider this risk in the therapeutic decision-making process.